Here's the question you clicked on:
alyssababy7
Solve the linear equation. (will write in comment) A. {-9/11} B. {-27/11} C. {-45/11} D. {-63/11}
|dw:1352515501659:dw|
multiply both sides by 9 to clear the fractions use parentheses carefully i will write it out
\[\frac{x-6}{-3}+\frac{x+9}{9}=x+4\]before we begin, is that right?
ok here we go \[\frac{x-6}{-3}+\frac{x+9}{9}=x+4\] \[9\times \left(\frac{x-6}{-3}+\frac{x+9}{9}\right)=(x+4)\times 9\] \[-3(x-6)+x+9=9x+36\] this is the only hard part, now remove the parentheses using the distributive law, combine like terms and then solve would you like me to continue?
yes continue please
\[-3(x-6)+x+9=9x+36\] remove parentheses get \[-3x+18+x+9=9x+36\] combine like terms get \[-2x+27=9x+36\] add \(2x\) to both sides get \[27=11x+36\] subtract \(36\) get \[-9=11x\] divide by \(11\) \[-\frac{9}{11}=x\]
the hard part is remembering to use parentheses when you clear the fractions then distribute etc